Assessment of strategic planning for the adoption of the blockchain technology - Luiz, Jonatan Pacheco (2020)
This thesis explores ways to infer if companies are diligently planning strategies to support the decision to adopt the blockchain technology. To that purpose, concepts already introduced in the strategic management literature are presented through a 9- steps framework. Then, information regarding attitudes on blockchain, gathered from secondary sources, is assessed vis-à-vis the framework. With this structured analysis of key variables and their context, it is possible to identify patterns, areas, processes or activities that are most likely to present problems. Considering factors like the FOMO (fear of missing out) effect, it is fundamental to ensure rational and accurate decision making in companies. Among the main findings are two warnings to managers: a possible overconfidence related to levels of knowledge and the lack of objective criteria to measure performance against competitors.